The role of personal hygiene on non complicated pediatric appendicitis patients - Bagus, Budhi Ida; Rumaisha, Azka; Suwardi, Suwardi; Dewi, Yudhani Ratih (International Surgery Journal, 2018)
Background: Appendicitis is an inflammation that occurs in appendix vermiformis and is the most common cause of abdominal pain. Appendicitis is also an indication of emergency abdominal surgery in children. The incidence of child appendicitis is 1.66 per 1000. If the diagnosis is delayed, 97% of cases of acute appendicitis will lead to perforation with a mortality rate of 5.1 per 1000 cases. The most common etiology of appendicitis is lymphoid tissue hyperplasia which represents one of the immune responses to infection. One of the infection factors was the poor personal hygiene level. This research aimed to discover personal hygiene level description in pediatric non complicated appendicitis. Methods: This research used descriptive quantitative observational research conducted in Moewardi General Hospital Surakarta. The sampling method was total sampling in appendicitis patient with, 33 respondents. Assessment in patients was calculated using personal hygiene scale questionnaire consisting of 12 items. The independent variable in this research was personal hygiene level, and the dependent variable was the incidence of pediatric appendicitis. Data were analyzed statistically for descriptive analysis. Results: The result showed that 51.5% of patients with pediatric appendicitis had poor personal hygiene. Conclusions: Pediatric appendicitis patient had poor personal hygiene level.